Efforts to Increase Early Detection of the State Security Unit Intelkam in Preventing Criminal Acts in the Blitar Police Jurisdiction - Hidayat, M Dwiki Darmawan (Indonesian Journal of Police Studies, 2024)
This research is motivated by the phenomenon of criminal acts of Currat in the Blitar Police area which requires a fast and precise solution. The main step that can be used as a solution is to prevent criminal acts of cursing, which is done through early detection. However, the success of early detection of Currat's criminal acts appears to be low. This is reflected in the ratios or statistics that show the lack of success in preventing Currat cases in this region. Therefore, in this research the management function is analyzed in an effort to increase early detection by the Blitar Police Department of Security and Security Unit in preventing the crime of currat and the condition of organizational resources that support efforts to increase early detection of the Blitar Police Department of Security and Intelligence and Security Unit in preventing cursing crimes is analyzed. The theories and concepts used include management theory, organizational resource theory, social penetration theory, the concept of first principles thinking, the concept of early detection, and the Currat crime concept. The method used in this research is qualitative. The results of this research indicate that the management function in increasing early detection of the Blitar Police Department of Security and Security Unit in preventing criminal acts of cheating has not been planned with prior priority. However, the implementation of early detection has been well organized, resulting in the identification of locations prone to cheating crimes. However, early detection has not succeeded in revealing the profile of potential perpetrators. Surveillance issues are limited to certain areas considered vulnerable, relying on advanced technology. Analysis of Curat's crime patterns is less in-depth, and community participation in providing information is still low, reducing the accuracy of information and understanding of Curat's crime patterns. Organizational resources are divided into supporting factors (human resources, facilities, infrastructure, methods) and inhibiting factors (budget not allocated in detail for early detection of cheating and minimal community involvement in providing information).